A Survey of Employee Perceptions of Information Privacy in Organizations - Woodman, Richard W.; Ganster, Daniel C.; Adams, Jerome; McCuddy, Michael K.; Tolchinsky, Paul D.; Fromkin, Howard L. (Academy of Management Journal, 1982)
In this study of employees in five multinational corporations, assessment was made of (a) employees' beliefs regarding the types of personal information stored by their companies, (b) the accuracy of those perceptions, (c) reactions to various internal and external uses of this personal information, and (d) evaluations of the companies' information handling policies and practices.